The Implementation of Online Formative Assessment in English Learning - Komang Lisna Kristiyanti (Journal of Educational Study, 2021)
The pandemic of COVID-19 is one of the major disasters in 2020 that have occurred throughout the world, including Indonesia. In the present situation and condition, in which most schools are currently implementing an online learning process, it is necessary to make sure that every students gain the information or knowledge that they must get as the result of the learning process. Hence, the formative assessment is in accordance with everyone's expectations that student must continue to gain information as their online learning outcomes. This study aimed to review other studies conducted by some previous researchers regarding the implementation of formative assessment in online learning environment. Since this kind of assessment was only recently applied in the COVID-19 pandemic situation, it is important to investigate the effect, as well as the perception of students and teacher in implementing formative assessment in online learning environment. A library research was conducted to collect the data. From this review study, it can be concluded that this assessment technique has the potential to be very useful to be implemented in English learning, both for teachers and students. There are correlation between motivation, self-efficacy, and strategic regulation of learning. The students and teacher also showed positive perception towards online formative assessment. Both the students and the teacher gained many beneficial things after the implementation of online formative assessment in English learning.